Primary aldosteronism : physiopathology and diagnosis - Araujo-Castro, Marta (Vitamins and hormones, 2026)
Primary Aldosteronism: Physiopathology and Diagnosis, Volume 130 focuses on the physiopathology and diagnosis of primary aldosteronism, covering some important topics such as Aldosterone: synthesis and regulation, Pathophysiology of primary aldosteronism, Prevalence of primary aldosteronism and screening indications, Clinical manifestations of primary aldosteronism and cardiometabolic risk, Diagnosis of primary aldosteronism: renin activity, renin concentration and aldosterone/renin ratio, Diagnosis of primary aldosteronism confirmatory test, Diagnosis of Primary Aldosteronism: Novel Workup Strategies and Biochemical Tools, and much more. Additional sections cover Genetics in primary aldosteronism, Low-renin hypertension, Adrenal venous sampling interpretation and other diagnostic lateralization tools in PA, and Aldosterona & Cortisol cosecretion.- Primary aldosteronism is the most frequent etiology of endocrine hypertension and is associated with a higher cardiometabolic risk than essential hypertension- The diagnosis of primary aldosteronism is usually performed in three steps: (1) case detection; (2) case confirmation, (which is not strictly necessary in all cases); and (3) subtype differentiation- Subtype classification has the main aim of identifying unilateral cases, who are candidates for surgery.